Christian-Muslim dialogue in the twentieth century - Siddiqui, Ataullah (New York St. Martin's Press, 1997)
The book describes the challenge of modernity faced by Muslims and Christians and the issue of religious pluralism. It describes Muslims' encounters with Christianity in the first half of this century and their participation in organized dialogues initiated by the Churches in the second half. It highlights their apprehensions and expectations in dialogue and issues of co-existence in the world today. The book focuses on six prominent Muslim personalities who represent a wide spectrum of Muslim opinion and three international organizations and their attitude towards dialogue.
The challenge of modernity -- The churches' move towards dialogue -- Muslims in dialogue: assessment and priorities -- Isma'il Raji al-Faruqi (1921-86) -- Mahmoud Ayoub (1935- ) -- Hasan Askari (1932- ) -- Khurshid Ahmad (1932- ) -- Mohammed Talbi (1921) -- Seyyed Hossein Nasr (1933- ) -- Discussion -- international organizations -- Discussion -- Conclusion.
Includes bibliographical references (pages 221-231) and index.
Keywords: Islam -- Relations -- Christianity; Christianity and other religions -- Islam